2014
DOI: 10.1111/iju.12530
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and prognosis in muscle‐invasive bladder cancer: The continuing controversy

Abstract: Abbreviations & AcronymsObjectives: To investigate the association between body mass index and clinicopathological features of bladder cancer, and to assess the prognostic value of body mass index in patients undergoing radical cystectomy for bladder cancer. Methods: The medical records of 714 patients who underwent radical cystectomy for bladder cancer were reviewed. The association of body mass index at surgery with clinicopathological features was examined, and the prognostic value of body mass index for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 29 publications
0
36
0
Order By: Relevance
“…Kwon et al [15] recently reported that overweight patients who underwent RC had more favourable pathological features and a better prognosis than those with normal BMI values. Quite the contrary, low BMI was a predictor for increased mortality and poor OS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kwon et al [15] recently reported that overweight patients who underwent RC had more favourable pathological features and a better prognosis than those with normal BMI values. Quite the contrary, low BMI was a predictor for increased mortality and poor OS.…”
Section: Discussionmentioning
confidence: 99%
“…However these findings stand in strong contrast to other studies’ results. As preoperative nutritional deficiency is a risk factor for increased mortality and poor overall survival (OS) after RC Kwon et al [15] found favorable pathological features and prognosis in obese patients after RC. Hafron et al [16] reported no significant association between higher BMI and disease-specific survival.…”
Section: Introductionmentioning
confidence: 99%
“…Although obesity is considered as an established risk factor for the development of renal cell carcinoma (RCC), it has been consistently reported that obesity is related to better pathological features and survival outcome in RCC [10,11]. However, in cases of prostate and bladder cancer, conflicting results have been reported between studies [12,13,15,16]. Interestingly, for prostate and bladder cancer, the influence of obesity on cancer-related outcomes was different depending on patients' ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, 15-20 % of all cancer deaths in the USA were probably because of excess body weight [6]. The relationship between obesity and mortality from cancer has also been investigated in urologic cancers, including kidney, prostate, and bladder [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation